A study on realistic literary features depicted in Greek epics (Based on Iliad and Odyssey) - Kumari, H. M. S. I. (Faculty of Graduate Studies - University of Kelaniya, Sri Lanka., 2024)
Myths, legends, folktales, and antiquities represent a distinct genre of storytelling that has been transmitted orally through generations to the present day. Among the literary forms constructed upon these narratives, the Epic (Maha Kavya) holds a significant place. The Iliad and the Odyssey, attributed to the great poet Homer and believed to have been composed in the 7th or 8th century BC, are two such major epics based on the myths prevalent in Greek society at the time. Regardless of the historical veracity of the events described, these works can be identified as reflections of a multitude of philosophical streams. Through the portrayal of heroic and divine figures, these epics illustrate complex character traits, social influences, daily life, and social inequalities prevalent in Greece, thereby highlighting realistic literary characteristics. Consequently, the primary objective of this study is to analyze the realistic literary features depicted in the Iliad and Odyssey. To achieve this, the study utilizes both primary and secondary data sources. Adopting a qualitative research methodology rooted in ethnographic inquiry, the study addresses the research problem of whether realistic literary characteristics are evident in these epics and, if so, in what manner they manifest. The analysis argues that while myths based on religion often seem distant from reality, the depiction of characters and events reflects human thinking, motivations, and social dynamics of the era, thus linking mythology to reality. It suggests a reconstruction of realities that can still be experienced, heard, and seen today. The study concludes that these myths represent a collection of diverse streams of thought which served as the seed for literary creation. Furthermore, it posits that these literary works were not merely for entertainment but represented the embryonic stages of the realistic thought processes that became a major discourse in the 19th century.
ග්‍රීක මහා කාව්‍යයන්හි නිරූපිත යථාර්ථවාදී සාහිත්‍ය ලක්ෂණ පිළිබඳ අධ්‍යයනයක් (ඉලියඩ් හා ඔඩිසි මහා කාව්‍යයන් ඇසුරෙන්)
Keywords: Myths; Epics; Realism; Literature